If philosophers went on a leadership course: A (serious) farce in three Acts. (August 2022) - Wilson, Suze; Lee, Hugh; Ford, Jackie; Harding, Nancy
Leadership development is big business, with business schools and private providers offering leadership development programmes claimed to help turn managers into wise, good and able leaders. Leadership development originated in philosophy and, in the Western tradition, dates back at least as far as Socrates. This article asks: how would philosophers qua wisdom-lovers [philo-sophes] respond to contemporary programmes? We use the dramatic licence offered by theatre to imagine Foucault, Butler, Kant, Hume and others participating in a leadership training course. As our play opens, we find them critiquing a 360-degree psychometric assessment instrument they have been asked to complete. Our highly select group argue it solicits docile, servile supplicants to the interests of neoliberal capitalism. They offer an alternative containing key questions putative leaders should explore. The script includes other dramatis personnae and a Chorus (the authors of this paper). Speeches and programme notes provide the necessary bones of an academic paper, such as literature reviews and philosophical contexts. We ask colleagues to join with us in reconnecting leadership development to its philosophical roots in an effort to foster wiser and more ethical leadership.